Analisis Tokoh dan Latar Belakang Terjadinya Konflik dalam Novel Kudasai Karya Brian Khrisna - Vinna Andina; Zaenal Arifin; Restoeningroem Restoeningroem (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2023)
This study aims to: 1 Know the analysis of the characters contained in the novel Kudasai by Brian Khrisna. 2. Describe the conflicts that occur in the novel Kudasai by Brian Krishna. The method used in this research is descriptive method. This method is used to analyze the characters and conflicts in the novel Kudasai by Brian Krishna. The results of the analysis show that the main character in the story is Chaka and additional characters Twindy, Anet, Romi, Deni, Ryan, Dimas who are the supporters of the story. To describe the conflict problems contained in the novel using data based on quotations that contain internal and external conflicts. The results of the conflict research show that internal conflicts in the novel Kudasai consist of: nervous feelings, forced feelings, feelings of love or affection, feelings of suspicion, feelings of anger, feelings of fear, feelings of guilt, feelings of anxiety, feelings of disappointment, feelings of sadness, feelings of hatred, and feelings upset, and external conflicts include physical conflicts and social conflicts.Keywords : Novel, Character, Conflict